Existence of solutions for fractional p-Laplacian differential equations with dual periodic boundary conditions - Wei Zhang; Yu Zhang; Jinbo Ni (Applied Mathematics in Science and Engineering)
This paper introduces a new concept of dual periodic boundary conditions. One of these conditions relates to the endpoints of an interval, while the other one involves two nonlocal positions within the interval. Under these boundary conditions, we establish the criteria for the existence of solutions for a fractional differential equation with p-Laplacian operator by using Mawhin's continuation theorem. An example is constructed for illustrating the obtained results.